Synergistic combinations of paclitaxel and withaferin A against human non-small cell lung cancer cells - Kyakulaga, Al Hassan (Oncotarget, 2020)
Platinum-taxane combination chemotherapy still represents the standard of care for advanced non-small cell lung cancer (NSCLC) with no targetable driver mutations. However, the efficacy of these drugs has plateaued at 10–14 months primarily due to dose-limiting toxicity, chemoresistance, and metastasis. Here, we explored the effects of withaferin A (WFA) alone and in combination with paclitaxel (PAC) on the growth, proliferation, migration, and invasion of human NSCLC cells. We show that the sensitivity of H1299 and A549 cells to concomitant treatment with PAC and WFA was greater than that of either PAC or WFA alone. Using the combination index and dose-reduction index, we demonstrated that various combinations (1:40, 1:20, 1:10) of PAC to WFA, respectively, were highly synergistic. In addition, PAC+WFA co-treatment synergistically inhibited colony formation, migration, invasion and increased the induction of apoptosis in H1299 and A549 cells. Interestingly, the synergism of PAC and WFA was not schedule-dependent but was enhanced when cells were pretreated with WFA indicating a chemo-sensitizing effect. Importantly, WFA was active against both PAC-sensitive (TS-A549) and PAC-resistant (TR-A549) cells both in vitro and in vivo. Mechanistically, WFA inhibits the proliferation of NSCLC cells via thiol oxidation. The effects of WFA were inhibited in the presence of N-acetyl cysteine and other thiol donors. Taken together, our results demonstrate the efficacy of WFA alone or alongside PAC on NSCLC cells and provide a strong rationale for further detailed testing in clinically relevant models for the development of PAC+WFA combination as an alternative therapeutic strategy for advanced NSCLC.